Effect of maternal diet on gut bacteria and autism spectrum disorder in offspring - Chen, Zilin; Wang, Xu; Hu, Yuchen; Zhang, Si; Han, Fei (Frontiers in Cellular Neuroscience, 2025)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder that manifests in early childhood, with its specific causes and pathogenesis remaining incompletely understood. The gut bacteria plays a pivotal role in host health and neurodevelopment. Maternal eating disorders may disrupt maternal gut bacteria and subsequently influence fetal and neonatal gut bacteria through the gut-placental axis and breastfeeding. This disruption can ultimately impact the microbial-gut-brain axis, the immune system, neurotransmitter dysregulation, and metabolite abnormalities, thereby increasing the risk of ASD in offspring. This paper reviews the adverse effects of bad maternal dietary habits, including high-sugar, high-salt, high-fat diets, alcohol consumption, dietary fiber deficiency, and the intake of ultra-processed foods, on the gut bacteria. It also explores the mechanisms by which gut microbiota disorder may induce ASD through the immune system, neurotransmitters, and metabolites. Additionally, the article proposes potential strategies to prevent ASD by adjusting dietary structures and enhancing gut bacteria health.